Hospital Preparedness for Natural Disaster: A Qualitative Study at Undata Regional General Hospital, Central Sulawesi - Andini, Intan Fitrah; Widjanarko, Bagoes; Suryawati, Chriswardani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Natural disasters pose significant threats to human life, and no region in Indonesia is immune. In 2018, Central Sulawesi faced its most devastating disaster, severely impacting various sectors, particularly hospitals. As the primary referral center in the province, Undata Hospital plays a crucial role in disaster response. This study utilized a descriptive qualitative research approach, collecting data through in-depth interviews, field observations, and document reviews. Undata Hospital has a natural disaster policy (Hospital Disaster Plan), with SOPs (general procedures), has a disaster response team (HDP team and the K3RS team), Financial resources come from the hospital's situational funds, the infrastructure needs remain unfulfilled, and the last training session was conducted in 2017. Undata Hospital disaster readiness is at a basic level. Despite having a disaster policy, it lacks socialization and specific SOPs for natural disasters. The disaster response teams are not fully functional, infrastructure needs are inadequately addressed, continuous training and simulations are insufficient, and funding for disaster preparedness is lacking